Quantitative and qualitative morphological diversity among nine cherry tomato (Solanum lycopersicum) genotypes grown under lowland conditions - ZULFIKAR DAMARALAM SAHID; ABDUL QADIR; MUHAMAD SYUKUR; KHARISMA FIRMAN ARIYANTO; ALDI KAMAL WIJAYA; PUNJUNG MEDARAJI SUWARNO; HENNY RUSMIYATI; ANDI NADIA NURUL LATHIFA HATTA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Sahid ZD, Qadir A, Syukur M, Ariyanto KF, Wijaya AK, Suwarno PM, Rusmiyati H, Hatta ANNL. 2026. Quantitative and qualitative morphological diversity among nine cherry tomato (Solanum lycopersicum) genotypes grown under lowland conditions. Biodiversitas 27 (6): d270622. https://doi.org/10.13057/biodiv/d270622. Cherry tomatoes are a type of tomato that has seen increasing market demand post-global pandemic as a healthy fruit. Cherry tomato cultivation is generally carried out in highlands and faces competition from other vegetable cultivation. Therefore, developing cherry tomato varieties adapted to lowland conditions is necessary. Developing new superior varieties requires basic information for selecting the diversity of the parents used. Therefore, this study aims to evaluate the morphological diversity of Institut Pertanian Bogor (IPB) cherry tomato lines as cross-breeding parents in further studies. The study was conducted at the lowland greenhouse teaching factory of the vocational school, Institut Pertanian Bogor, Bogor, using automated irrigation and fertigation systems and a single-factor randomized complete block design. The results of this study indicate that there is diversity among nine Institut Pertanian Bogor cherry tomato lines (hybrid and non-hybrid lines) that have the potential to be used as parents in the development of new superior varieties. The seed germination percentage measured in this study varied (80-95%), with early flowering and harvest times (26 and 62 days after transplanting). The average fruit length, diameter, and weight (3.28 cm, 19.24 mm, and 7.23 g) measured in this study showed a vast morphological divergence, making them potential parent lines in cherry tomato breeding. Cluster analysis of nine genotypes based on their morphological characteristics resulted in three main groups, from which parents for breeding were selected. IPBTC 147 forms a distinct group due to its unique morphological characteristics, both quantitative and qualitative, which significantly differ from other genotypes, particularly in its fruit shape and color. This genotype has an average fruit weight of 5 g with the longest fruit stalk length (2.27 cm). The yellow color of this fruit has the potential to produce high diversity in the F2 when crossed with red fruit color. The morphological performance information of this research is expected to serve as a consideration for selecting parents for the development of cherry tomatoes adapted to lowlands.